(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
In the present study an unsteady convective diffusive mass transfer in a flow of viscoelastic fluid flow in a concentric annulus with applied magnetic field is considered. The velocity is analytically obtained using no-slip condition. The species equation is solved by adopting a dispersion model used by Gill and Sankarasubramanian approach. The parameters like dispersion and convection coefficients which arise in the analysis are plotted against absorption parameter for different values of Hartmann number and viscoelastic parameter. The effect of viscoelastic parameter is to increase the convective coefficient and dispersion coefficient. Dispersion increases with absorption but convection decreases. The results are numerically evaluated and graphically depicted.